Pharmacokinetics of caffeine and its metabolites in plasma and urine after consuming a soluble green/roasted coffee blend by healthy subjects - Martínez-López, Sara; Sarriá, Beatriz; Baeza, Gema; Mateos, Raquel; Bravo-Clemente, Laura (Food research international, 2014)
Coffee is widely consumed worldwide; therefore, the methylxanthines contained in coffee, mainly caffeine (CF), are among the most abundant bioactive compounds in our diet. In the present work, the bioavailability and metabolism of methylxanthines in a commercial soluble green/roasted coffee blend was studied. After a 3-day restriction of methylxanthine-containing foods, fasting healthy subjects (12 men and women) consumed the coffee product containing 70.69mg CF and 0.119mg theobromine (TB). Plasma samples were taken before (t=0h) and after coffee consumption at different time points (0.5, 1, 1.5, 2, 3, 4, 5, 6, 8, 9, 10 and 12h). Urine was collected at baseline (−2–0h) and at different intervals (0–2, 2–5, 5–8, 8–12 and 12–24h). Samples were analyzed by HPLC-DAD and LC–MS-QToF, and pharmacokinetic parameters were calculated. CF was the main methylxanthine found in plasma (Cmax=10.50μM, Tmax=1.2h). In addition, seven methylxanthines and methyluric acids were detected between 0.5 and 12h after coffee intake, paraxanthine (PX) being the major metabolite (Cmax=3.36μM), followed by 1-methyluric acid (1-MU; Cmax=1.44μM) and 1-methylxanthine (1-MX; Cmax=1.27μM), identified in plasma samples for the first time. In 24h urine, eleven methylxanthines and methyluric acids were detected, 1-MU being the major metabolite (Cmax=150.52μM, Tmax=12h) amounting to 67.7% of the total urinary metabolites. In conclusion, a rapid absorption, metabolization and excretion of caffeine and its derived methylxanthines and methyluric acids have been observed after consumption of a green/roasted coffee product. •Novel findings on caffeine metabolites in plasma and urine after coffee intake•8 metabolites were identified in plasma, including 1-methylxanthine and 1-methyluric.•11 urine metabolites (tri- di- & mono-methylxanthines & methyluric acids) detected•LC–MS-QToF and HPLC-DAD (single run) were used with minimum sample preparation.•Caffeine is rapidly absorbed and metabolized after coffee intake by healthy subjects.